BIM-Integrated Collaborative Robotics for Application in Building Construction and Maintenance - Follini, Camilla; Magnago, Valerio; Freitag, Kilian; Terzer, Michael; Marcher, Carmen; Riedl, Michael; Giusti, Andrea; Matt, Dominik Tobias (Robotics (Basel), 2021)
The application of robotics in construction is hindered by the site environment, which is unstructured and subject to change. At the same time, however, buildings and corresponding sites can be accurately described by Building Information Modeling (BIM). Such a model contains geometric and semantic data about the construction and operation phases of the building and it is already available at the design phase. We propose a method to leverage BIM for simple yet efficient deployment of robotic systems for construction and operation of buildings. With our proposed approach, BIM is used to provide the robot with a priori geometric and semantic information on the environment and to store information on the operation progress. We present two applications that verify the effectiveness of our proposed method. This system represents a step forward towards an easier application of robots in construction.